Purification and Characterization of Gigantoxin-4, a New Actinoporin from the Sea Anemone Stichodactyla Gigantea - Bo Hu, Wei Guo, Liang-hua Wang, Jian-guang Wang, Xiao-yu Liu, Bing-hua Jiao (International Journal of Biological Sciences, 2011)
A new Cytolysin, termed as Gigantoxin-4, was isolated from the sea anemone Stichodactyla gigantea and found to be highly homologous with Cytolysin-3 (HMg III) from Heteractis magnifica, RTX-A from Radianthus macrodactylus, and Sticholysin-1 (St I) and Sticholysin-2 (St II) from Stichodactyla helianthus (homology 82%, 86%, 82% and 86% respectively). Its 20 N-terminal residues were identified and the full-length cDNA sequence was obtained by reverse transcription-polymerase chain reaction (RT-PCR). Multiple sequence alignments with other Cytolysins of the actinoporin family clearly indicated that Gigantoxin-4 belongs to this protein family. SDS-PAGE electrophoresis showed that this new actinoporin had a molecular mass of about 19 kDa, and possessed a high hemolytic activity to human erythrocytes (HA50= 40 ng/ml), which was inhibited by pre-incubation with sphingomyelin (SM) or SM-cholesterol mixtures. Our in vivo experiments showed that Gigantoxin-4 had wide toxicity to the rat cardiovascular system and the respiratory system. A concentration of 30μg/kg Gigantoxin-4, i.v. produced a positive inotropic effect on the rat heart although final cardiovascular failure was inevitable, and 60μg/kg Gigantoxin-4 caused respiratory arrest rapidly resulting in rat death. HE staining indicated pathological changes in various organs and tissues after i.v. administration of Gigantoxin-4.